Preliminary Studies on Chemical Weed Control in Eucalyptus (Hybrid) Nursery - Swami Rao, N.; , Dasappa; Singh, C. D. (Indian Forester, 1985)
Weeds adversely affect the germination and growth of seedling in the Eucalyptus Hybrid nurery beds. Manual weeding which is generally followed is time consuming, difficult and less effective. In order to overcome this problem a study was undertaken for effective control of weeds in Eucalyptus hybrid nursery by means of pre-emergence weedicides viz.basaline (Profluralin), Pendimethaline (stanp 30 EC), ronster (Oxadiazen) and Simazine. They were applied to nursery beds as pre-emergence spray, at 1.5, 1.5, 1.5 and 1 kg/ha respectively. Basalin was most effctive in controlling both dicot and monocot weeds followed Pendimethaline and Ronster. Simazine was lethal to both Eucalyptus and weed seed germination. Seedling of Eucalyptus in Basaline treated plots were more in number(152/sq ft.) taller (24 cm) and healthier compared to other weedicides treatments. Maximum nunber of dicots and monocot weeds were found in control plots , consequently seedling growth was very much suppressed. The studies indicated that pre- emergence chemical weedicides could be effectively used to control nursery weeds and that basaline weedicides is more effective in controlling both dicots and monocot weeds and appears to be suitable chemical weedicides for Eucalyptus hybrid nurseries.